STUDIES OF STRUCTURAL AND OPTICAL PROPERTIES OF HYBRID ORGANIC-INORGANIC PEROVSKITE FOR COLOUR TUNABILITY IN VISIBLE REGION - REBECCA , LEONG WEI XIAN (2019)
Metal halide perovskites are crystalline materials known for their excellent optoelectronic properties and solution processable making it suitable for optoelectronic application.